Phosphorus migration in an unconfined aquifer using modflow and Mt3dms. - Saghravani, Seyed Reza; Mustapha, Sa'ari; Ibrahim, Shaharin; Yusoff, Mohd. Kamil; Saghravani, Seyed Fazlolah (Vilnius Gediminas Technical University, 2011)
The rapid rate of urbanization and increasing demand for water in agriculture and industry are the reasons for considering groundwater as a main source of water. This can be a prologue to contamination of groundwater. Phosphorus as a type of nutrient that is derived from fertilizers has adverse effect on surface and subsurface water. The aim of this study was to monitor groundwater quality and the fate of contamination via three dimensional finite-different groundwater flow simulation (i.e. Visual MODFLOW version 4.2.). The study area was the campus of University Putra Malaysia. The monitoring indicated that the concentration of phosphorus is higher than those imposed by the standard of the Malaysian Department of Environment (DOE). Results of contamination transport modelling revealed the different rates of phosphorus transport in layers at the end of simulation period.